Phylogenetic analysis in the clinical risk management of an outbreak of hepatitis C virus infection among transfused thalassaemia patients in Italy. (September 2021) - Mazzucco, W.; Chiara di Maio, V.; Bronte, F.; Fabeni, L.; Pipitone, R.M.; Grimaudo, S.; Ferraro, D.; Marotta, C.; Aragri, M.; Macaluso, M.; Vitale, F.; Di Raimondo, F.; et al.
Summary: Background: Occurrence of hepatitis C virus (HCV) infection is reduced by effective risk management procedures, but patient-to-patient transmission continues to be reported in healthcare settings. Aim: To report the use of phylogenetic analysis in the clinical risk management of an HCV outbreak among 128 thalassaemia outpatients followed at a thalassaemia centre of an Italian hospital. Methods: Epidemiological investigation and root-cause analysis were performed. All patients with acute hepatitis and known chronic infection were tested for HCV RNA, HCV genotyping, and NS3, NS5A, and NS5B HCV genomic region sequencing. To identify transmission clusters, phylogenetic trees were built for each gene employing Bayesian methods. Findings: All patients with acute hepatitis were infected with HCV genotype 1b. Root-cause analysis, including a lookback procedure, excluded blood donors as the source of HCV transmission. The phylogenetic analysis, conducted on seven patients with acute infection and eight patients with chronic infection, highlighted four transmission clusters including at least one patient with chronic and one patient with acute HCV infection. All patients in the same cluster received a blood transfusion during the same day. Two patients with acute hepatitis spontaneously cleared HCV within four weeks and nine patients received ledipasvir plus sofosbuvir for six weeks, all achieving a sustained virological response. Conclusion: Combined use of root-cause analysis and molecular epidemiology was effective in ascertaining the origin of the HCV outbreak. Antiviral therapy avoided the chronic progression of the infection and further spread in care units and in the family environment.